1988
DOI: 10.1152/ajpheart.1988.255.6.h1276
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine potentiates human platelet activation but is not an aggregating agent

Abstract: Epinephrine can in certain in vitro conditions induce the aggregation of human platelets and could play an important role in vivo in the appearance of thrombotic disorders when catecholamine levels are increased. This study examines some functional and biochemical responses to epinephrine. Epinephrine induces the aggregation and serotonin secretion of human platelets in citrated plasma. This is not due to a direct effect of citrate itself, such as the lowering of plasma free Ca2+ but more likely to the generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
73
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 0 publications
12
73
1
Order By: Relevance
“…However, in agreement with previous in vitro studies, 12 -" we found that low concentrations of Epi per se did not activate platelets in vitro. We have previously shown that Epi infusion in vivo enhances platelet aggregability at a dose of 0.4 nmol • kg" 1 • min" 1 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in agreement with previous in vitro studies, 12 -" we found that low concentrations of Epi per se did not activate platelets in vitro. We have previously shown that Epi infusion in vivo enhances platelet aggregability at a dose of 0.4 nmol • kg" 1 • min" 1 .…”
Section: Discussionsupporting
confidence: 93%
“…At supraphysiological concentrations (^1 /imol/L) Epi per se has been reported to induce aggregation in citrated but not hirudin-treated plasma. 12 -0 - 30 Enhancement of platelet responsiveness to these high concentrations of Epi in citrated plasma may 12 or may not B be dependent on enhanced thrombin formation. However, with wholeblood flow cytometry and single-cell counting, Shattil et al" have demonstrated that fibrinogen receptor exposure and fibrinogen binding are enhanced by high Epi concentrations under both low-and high-calcium conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is well-known that inhibition of adenylyl cyclase per se is not sufficient to trigger platelet aggregation (3), and agonists such as epinephrine, acting by activation of Gi only, do not promote platelet aggregation (32). However, we show here that a high concentration of ADP (100 µM) induces aggregation of P2Y 1 -/-mice platelets through activation of the P2cyc receptor ( Figure 4).…”
Section: Discussionmentioning
confidence: 45%
“…Platelets were directly fixed in the aggregation cuvette with 2.5% glutaraldehyde in 0.1 M cacodylate buffer, pH 7.2, containing 2% sucrose. Platelets were then processed as described previously (32). Ultrathin sections were observed under a Philips CM120 Biotwin electron microscope (Philips Consumer Electronics B.V., Eindhoven, The Netherlands) at 120 kV.…”
Section: Methodsmentioning
confidence: 99%